Terpaan YouTube Series dan Persepsi Pemasaran Interaktif di Twitter terhadap Keputusan Pembelian Layanan Subscriptions Video on Demand (SVOD) Netflix - Yuan Stephanie; Djoko Setyabudi; Tandiyo Pradekso (Interaksi Online, 2021)
Although Netflix has become a pioneer of SVOD services in Indonesia, a report released by Media Partners Asia (MPA) as of January 2021 shows Netflix in fourth position with a total of 850,000 subscribers after Disney+ Hostar, Viu, and Vidio. This study aims to determine the influence of YouTube series “Pensi Netflix” exposure and the perception of interactive marketing on Twitter towards purchase decision of Netflix's subscriptions video-on-demand (SVOD) service. The sampling technique used in this research is non-probability sampling with accidental sampling technique. The theory used is Cognitive Response Theory and Elaboration Likelihood Model. The results of hypothesis testing using simple linear regression analysis show that the research is not significant or there is no influence between the X1 variable (YouTube series exposure) on Y (purchase decision) with a significance value of 0.155. Then, based on the results of the H2 test using simple linear regression analysis, a significance value of 0.135 was obtained, which means that it is not significant between the variables X2 (perception of interactive marketing) and Y (purchase decisions).